Studies on Bioethanol Production from Rice Straw by Saccharomyces cerevisiae - Singh, Brajeshwar; Choudhry, Neeru (Journal for Research in Applied Sciences and Biotechnology, 2022)
The present study aims to determine the bioethanol producing potential of locally isolated Saccharomyces cerevisiae strain using Rice straw as a substrate. Fifteen yeast strains were isolated from fruit sample (Apple, Papaya, Sugarcane, Grapes, Orange, Pineapple) and Kaladi samples collected from local markets of Jammu and Udhampur district respectively. Potential yeast isolates were identified on the basis of morphological and microscopic characteristics which were similar to that of MTCC 170 culture procured from IMTECH-Chandigarh. Out of 15 isolates, 14 show a positive change in the color of screening medium indicating the production of ethanol. S-9 culture was further selected based on its highest bioethanol producing ability of 17.88 mg/mL at 24 h of fermentation on YEPD medium and hence chosen for the fermentation of rice straw hydrolysate. Rice straw was subjected to alkaline and acidic pretreatment which was followed by enzymatic hydrolysis. Ethanol Fermentation of the total Rice Straw Hydrolysate obtained after pretreatments using S-9 culture revealed maximum ethanol concentration of 12.26 mg/mL at 24h having fermentation efficiency of 69.5%, 50.7% of sugar conversion occur during the fermentation process and volumetric productivity of 0.1702 g/L/h. Ethanol content per gram of sugar utilized was estimated to be 0.168g/g. Further, S-9 culture show the maximum efficiency for bioethanol production on YEPD medium at temperature of 30ºC, pH of 5.6 and under static conditions.